The Relationship of Instructor Interpersonal Communication with Student Participation in LKP Ida Teratai Payakumbuh City - Melia Sari, Putri; Natsir, MHD (Universitas Negeri Padang, 2023)
This research is motivated by the low participation of learning residents at LKP Ida Teratai Payakumbuh City. This type of research is quantitative research with a correlational approach. The population in this study were residents studying sewing courses at LKP Ida Teratai Payakumbuh City. Sampling in this study used a saturated sampling technique, namely the entire population was used as a sample (24 people). The data collection technique uses a questionnaire with a data collection tool using a questionnaire. Data analysis uses the percentage formula and rank order correlation formula. The results of this study indicate that the interpersonal communication of instructors at LKP Ida Teratai Payakumbuh City is not well implemented, the participation of learning residents at LKP Ida Teratai Payakumbuh City is low, there is a significant relationship between interpersonal communication of instructors an the participation of citizens learning at LKP Ida Teratai Payakumbuh City.